The route of infection with Leptospira interrogans serovar Copenhageni affects the kinetics of bacterial dissemination and kidney colonization. - Nisha Nair; Mariana Soares Guedes; Catherine Werts; Maria Gomes-Solecki (Public Library of Science (PLoS), 2020)
The goal of this study was to characterize how natural routes of infection affect the kinetics of pathogenic Leptospira dissemination to blood and kidney. C3H/HeJ mice were sublethally infected with L. interrogans serovar Copenhageni FioCruz L1-130 (Leptospira) through exposure of a dermis wound and through oral and nasal mucosa, in comparison to uninfected mice and to mice infected via standard intraperitoneal inoculation. In striking contrast to oral mucosa inoculation, transdermal and nasal mucosa infections led to weight loss, renal colonization and inflammation, as previously observed for conjunctival and intraperitoneal infections. However, the timing at which Leptospira gained access to blood, as well as Leptospira' colonization of the kidney and shedding in urine, differed from intraperitoneal infection. Furthermore, a comparative analysis of transcription of pro-inflammatory mediators in kidney and total immunoglobulin isotyping in serum from infected mice, showed increased innate immune response markers (KC, MIP-2, TNF-α) and lower Th1 associated IFN-γ in kidney, as well as lower Th1 associated IgG2a in mice infected through the nasal mucosa as compared to intraperitoneal infection. We conclude that the route of infection affects the timing at which Leptospira gains access to blood for dissemination, as well as the dynamics of colonization and inflammation of the kidney.